Analisis Yuridis Perselisihan dan Pertengkaran Sebagai Pemicu dalam Kasus Perceraian di Indonesia - Miftah Agna Fin Janah; Ellys Kurnia Dewi; Endah Lestari; Resti Dian Luthviati (Journal of Law, Society, and Islamic Civilization, 2026)
This journal discusses divorce in the legal context and the factors that trigger rifts in marriage. This journal aims to provide a deeper understanding of how domestic disputes and conflicts are positioned as legal grounds for divorce and how judges assess and consider them in judicial practice. This study employs a normative legal research method with a qualitative descriptive approach. The primary focus of this study is to examine law as norms, rules, principles, doctrines, and legal theories to address the legal issues raised. Data collected for this study through a literature review, which serves as the primary foundation of the research, includes an in-depth analysis of relevant information sources, literature reviews, and court decisions related to divorce. The main contributing factors include poor communication n, economic issues, domestic violence, and infidelity. The results of the analysis indicate that in some cases, irreconcilable disputes lead to divorce decisions motivated by the couple’s inability to live harmoniously. Persistent disputes demonstrate that a legal approach alone is insufficient. Synergy is required between preventive education to build harmonious families and maximum mediation within the judicial system to repair the rift before a final decision is reached.